Preliminary analysis of eddy current and iron loss in magnetic gear in electric vehicle - Mohd Firdaus Mohd Ab Halim; Erwan Sulaiman; Mahyuzie Jenal; Raja Nor Firdaus Kashfi Raja Othman; Syed Muhammad Naufal Syed Othman (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The inclusion of a high energy density permanent magnet into magnetic gear improves the machine's torque density. However, it also contributes to eddy current loss, especially in a high-speed application such in electric vehicle. In this paper, the losses from eddy current and iron loss are investigated on concentric magnetic gear (CMG). Torque multiplier CMG is designed with 8/3 gear ratio for this study. Iron loss and eddy current loss are compared and discussed. Based on this study, eddy current loss contributes to almost 96% of the total loss. This finding is hoped to direct the researcher to focus more on reducing loss associated with eddy current loss.